Dismissal Of Civil Servants Those Who Commit Office Crimes Based On The Court Ruling Which Has Permanent Legal Force - Suparno, Suparno (Islamic Research Publiser, 2023)
The existence of differences in interpretation of PTDH legal norms for civil servants who commit office crimes based on court decisions that have permanent legal force causes differences in the application of law enforcement in practice, some are dishonorably dismissed, and some are not dismissed. This studi is a normative legal research method, using a statutory approach and a conceptual approach, analysis of legal materials is carried out in a qualitative juridical manner. The research results show that, First; The PTDH civil servant procedure begins with a temporary dismissal, then if the investigation is stopped or declared acquittal based on a court decision that has permanent legal force (inkracht van gewijsde), then the civil servant concerned is reactivated. However, if the civil servant concerned is sentenced to a criminal sentence based on a court decision that has permanent legal force (inkracht van gewijsde), then the PTDH of the civil servant is carried out by the Governor as the Civil Service Development Officer. Second; The legal remedy that can be taken by civil servants who have been sentenced to PTDH is to submit an Administrative Appeal to the State Civil Apparatus Advisory Body (BPASN). In the event that the civil servant concerned is not satisfied with the BPASN decision, the civil servant can submit legal action to the State Administrative High Court (PTTUN). Furthermore, if the civil servant concerned cannot accept the PTTUN decision, then the person concerned can submit a cassation legal action to the Supreme Court.